SHARIA MICROFINANCE INSTITUTION BUSINESS MODELS IN INDONESIA - Yoga Adipradana yoga; Muhammad Faris; Andoyo Andoyo; Mirza Mirza (SEAN Institute, 2022)
Islamic Microfinance Institutions (MFIs) have grown very rapidly in the last 10 years in Indonesia. In 2015, the number of IMFI reached more than 5,000. As a business and social entity, IMFI has various business models, ways of providing services and managing business to achieve its goals. This study aims to determine IMFI's business model. Methodology/Technique – This study used a qualitative approach using the Robert K. Yin case study technique. The subject of this research is IMFI in Indonesia which was selected purposively with the manager as the key informant. Findings – The result is that the IMFI business model is determined by eight elements, namely: organizational orientation, business and social functions, sources of capital and allocation, investors and customers, use of financing, types of contracts, allocation techniques, and membership. Novelty – The elements that determine IMFI, will form the IMFI business model that determines how IMFI carries out its business activities to achieve organizational goals.